2010
DOI: 10.1088/0963-0252/19/3/034020
|View full text |Cite
|
Sign up to set email alerts
|

Underwater electrical wire explosion

Abstract: A brief review of the results obtained in recent research of underwater electrical wire explosions using microsecond and nanosecond generators is presented. It was shown that the increase in the rate of energy input into the exploding wire allows one to increase the wire temperature and amplitude of shock waves (SWs). Estimated energy deposition into Cu and Al wire material of up to 200 eV/atom was achieved. In microsecond time scale wire explosion, a good agreement was attained between the wire resistance cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…2. One can see that the discharge is aperiodic, which is typical for underwater electrical explosion of wires 18,19 characterized by fast phase transitions of exploding wires: solid state-liquid-vapor-plasma. The main energy deposition to the exploding wires occurs during the formation of plasma that is rather low-temperature (several eV) and low-ionized, i.e., the resistance of each exploded wire increases up to 8 X.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2. One can see that the discharge is aperiodic, which is typical for underwater electrical explosion of wires 18,19 characterized by fast phase transitions of exploding wires: solid state-liquid-vapor-plasma. The main energy deposition to the exploding wires occurs during the formation of plasma that is rather low-temperature (several eV) and low-ionized, i.e., the resistance of each exploded wire increases up to 8 X.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…First, when the fiber was placed in the original wire array having a diameter of 30 mm, we obtained [see waveform (a) in Fig. 3] a drastic decrease in the laser intensity starting at time delay s d $ 0.45 ls with respect to the beginning of the wires' explosion (i.e., with respect to the beginning of the explosion accompanied by the generation of SSWs and at the time when a fast decrease in the discharge current is obtained 18,19 ), followed by a rather sharp and short ($100 ns time duration) recovery of the light intensity (first peak). The decrease in the light intensity can be explained by the fiber's decreased transparency (change of density and, respectively, refraction index) because of its interaction with SWs generated by the explosion of adjacent wires.…”
Section: Experimental Setup and Resultsmentioning
confidence: 99%
“…This strips the blockage attached to the surface of the seepage channel, reduces capillary force and surface tension, improves percolation ability and promotes gas desorption. Repeated action induces fatigue fracture, decreases various mechanical properties and expands the effective area of various functions [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Mechanism Of Repetitive Pulse Shock Wave Stimulationmentioning
confidence: 99%
“…It would be very difficult to exceed the aforementioned efficiency in the case of electrical discharge in water. Nevertheless, Krasik with coworkers [7] conducted a research of underwater electrical wire explosions using microsecond and nanosecond generators. It was observed that the increase in the rate of energy input into the exploding wire allows one to increase the wire temperature and amplitude of shock waves.…”
Section: Introductionmentioning
confidence: 99%
“…The highenergy density plasmas in Z-pinches could be applied for intense x-ray sources [7], astrophysics research [8], inertial confinement fusion [9], etc. While a major driving force of researching electrical explosions was to ascertain the early stage of Z-pinches, the abundant physical and chemical processes during the explosion also draw scholars' attention to studying the subjects of shock waves [10,11], nanomaterial preparations [12], plasma ignition [13], etc. For the above industrial applications, the pulsed power generator is usually compact and convenient for scholars to pursue fundamental research in their laboratories, and the electrical current density (energy deposition rate) could be relatively small (slow explosion, <10 8 A/ cm 2 ).…”
Section: Introductionmentioning
confidence: 99%